2020
DOI: 10.1099/acmi.0.000110
|View full text |Cite
|
Sign up to set email alerts
|

Experimental exposure of Burkholderia pseudomallei crude culture filtrate upregulates PD-1 on T lymphocytes

Abstract: Burkholderia pseudomallei is the causative agent for melioidosis. Because of its intracellular nature, the bacterium is capable of replicating within a plethora of eukaryotic cell lines. B. pseudomallei can remain dormant within host cells without symptoms for years, causing recrudescent infections. Here, we investigated the pathogenesis mechanism behind the suppression of T cell responses by B. pseudomallei . Peripheral blood mononuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…While this may represent a unique inflammatory response to melioidosis, this lack of acquisition of a polyfunctional T cell response could also represent T cell exhaustion. Evidence of pathologic T cell exhaustion is limited in melioidosis but increased T cell expression of PD-1 can be induced during B. pseudomallei infection in vitro [ 43 , 44 ]. In our study, the overall increase in both T cell population frequency and effector memory phenotype over time in survivors suggests that any active T cell suppression during acute infection improves within weeks, and that T cell memory responses that develop may potentially provide immunity in the event of future exposure to B. pseudomallei .…”
Section: Discussionmentioning
confidence: 99%
“…While this may represent a unique inflammatory response to melioidosis, this lack of acquisition of a polyfunctional T cell response could also represent T cell exhaustion. Evidence of pathologic T cell exhaustion is limited in melioidosis but increased T cell expression of PD-1 can be induced during B. pseudomallei infection in vitro [ 43 , 44 ]. In our study, the overall increase in both T cell population frequency and effector memory phenotype over time in survivors suggests that any active T cell suppression during acute infection improves within weeks, and that T cell memory responses that develop may potentially provide immunity in the event of future exposure to B. pseudomallei .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Menon et al. (2020) ( 116 ) demonstrated up-regulation of PD-1 on T cells in vitro , upon exposure to crude culture filtrate antigens of B. pseudomallei and suggested that this possibly contributes to deprived immune surveillance and pathogenesis.…”
Section: Cell-mediated Immunity and B Pseudomalleimentioning
confidence: 99%
“…According to a study by Khakhum et al. (2019) ( 116 ), IgG and their subclasses are inevitably significant in the detection of B. pseudomallei infection. Besides, a few scientific findings revealed that a discerning absence of one or more IgG sub-classes likely increases the susceptibility to recurrent infections or extend the course of an established infection.…”
Section: Cell-mediated Immunity and B Pseudomalleimentioning
confidence: 99%
See 1 more Smart Citation
“…Three bacterial strains were used: two isolates of B. pseudomallei clinical isolates obtained from University Malaya Medical Center (UMMC), OB (WT, INSDC: APLK00000000.1) and OS (SCV, INSDC: APLL00000000.1) and K9 (B. pseudomallei K96243) isolated from a melioidosis patient in Thailand and is commonly used as a reference strain. Characterization of all strains were performed using analytical profile index API 20NE (BioMrieux) test and PCR assay specific for B. pseudomallei (Menon et al, 2020). All of them were cultured in Luria-Bertani (LB) broth in a shaking incubator (37°C at 200 rpm).…”
Section: Bacterial Strains and Infectionmentioning
confidence: 99%